Growth performance and cost-benefit analysis of brackishwater fin fishes (Mugil cephalus and Rhinomugil corsula) with prawn (Macrobrachium rosenbergii) in polyculture at coastal ponds (Journal of the Asiatic Society of Bangladesh, Science, 2021)
The study was carried out to observe growth, production and profit of prawn, stripped mullet (Mugil cephalus) and corsula mullet (Rhinomugil corsula) at different stocking ratio under polyculture in the Bagerhat district for four months. The experiment was designed as a randomized block design and had three treatments based on stocking ratio with three replicates in each treatment. Juveniles of prawn (Macrobrachium rosenbergii) and fingerlings of fin fishes (stripped mullet and corsula mullet) were stocked at a stocking ratio of 3:1:1, 4:1:1 and 5:1:1/m2 in T1, T2 and T3, respectively. Prawn and fin fishes were fed with a commercial diet and farm made formulated feed on a daily basis. Recorded water quality parameters were within suitable ranges of prawn and fish culture. Higher growth (43.0 g) of the prawn was achieved in T1 followed by T2 (41.0 g) and T3 (38.0 g), but prawn growth was not significantly different between T1 and T2. The growth and survival rate of prawn, stripped mullet and corsula mullet were lower in T3, where the stocking ratio was higher. Higher production of the prawn was obtained in T2 (1148.0 kg/ha) than those of T1 (954.6 kg/ha) and T3 (1083.0 kg/ha). But significantly (p